Developing Contextual-Based Thematic Worksheets to Improve Critical Thinking Skill - Wonda, Hiwa (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study aims to develop contextually based Student Worksheets that can improve students' critical thinking skills. In addition, this study also aims to meet the needs of students and teachers for contextual-based student worksheets so that they can more easily understand the material and have interesting worksheets to use. This research is development research involving 22 subjects: teachers and grade IV students of SD Inpres Naikoten Kupang. The object of this study is student worksheets based on contextual approaches to improve students' critical thinking skills. Data collection is done through observation, questionnaires, and documentation. The data were analyzed using qualitative and quantitative data analysis. Furthermore, this study applies the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The result of this research is a product in the form of contextual-based student worksheets that have been tested for feasibility by material experts, linguists, and media experts. In addition, through student and teacher response tests, it was found that these student worksheets were effective, interesting, and practical to use by research subjects. This research succeeded in developing contextual-based student worksheets to improve students' critical thinking skills. The results showed that these student worksheets were effective and practical to use by teachers and students. Thus, this approach can effectively meet contextual needs in learning and improve students' critical thinking skills.